A Perspective on Polylactic Acid-Based Polymers Use for Nanoparticles Synthesis and Applications - Casalini, Tommaso; Rossi, Filippo; Castrovinci, Andrea; Perale, Giuseppe (Frontiers in Bioengineering and Biotechnology, 2019)
Polylactic acid (PLA) – based polymers are ubiquitous in the biomedical field thanks to their combination of attractive peculiarities: biocompatibility (degradation products do not elicit critical responses and are easily metabolized by the body), hydrolytic degradation in situ, tailorable properties and well–established processing technologies. This led to the development of several applications, such as bone fixation screws, bioresorbable suture threads and stent coating, just to name a few. Nanomedicine could not be unconcerned by PLA–based materials as well, where their use for the synthesis of nanocarriers for the targeted delivery of hydrophobic drugs emerged as a new promising application. The purpose of the here presented review is twofold: on one side, it aims at providing a broad overview of PLA–based materials and their properties, which allow them gaining a leading role in the biomedical field; on the other side, it offers a specific focus on their recent use in nanomedicine, highlighting opportunities and perspectives.